《澳門旅遊業發展總體規劃》文本建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

澳門《新城區總體規劃方案》之建議 - Pinheiro, Francisco Vizeu (澳門研究, 2017)

⼆⼗世紀澳⾨錯位的記憶——《神州在望》作品簡析. - Zhou, L. (Journal of Macau Studies, 2017)

User Preference on Artificial Reverberation and Delay Time Parameters - Pestana, Pedro Duarte; Reiss, Joshua; Barbosa, Álvaro (Journal of the Audio Engineering Society, 2017)
1 citations (Crossref) [2022-09-21] GSCC: 0000010

The impact of multimodal digital games in children’s learning environments - Martins de Abreu, F.; Barbosa, Alvaro (2017)

Sounding Architecture: Inter-Disciplinary Studio at HKU - Barbosa, Alvaro; Tsang, Thomas (Proceedings of the International Conference on New Interfaces for Musical Expression, 2017)
Sounding Architecture, is the first collaborative teaching development between Department of Architecture and Department of Music at the University of Hong Kong (HKU), introduced in Fall 2016. In this paper we present critical observations about the studio after a final public presentation of all projects. The Review was conducted with demonstrations by groups of students supervised by different Lecturer, in each case focusing on a different strategy to create a connection between Sound, Music, Acoustics, Space and Architectural Design. There was an assumption that the core working process would have to include the design of a new musical instrument, which in some cases became the final deliverable of the Studio and in other cases a step in a process that leads to a different outcome (such as an architectural Design, a performance or social experiment). One other relevant aspect was that Digital technology was used in the design and fabrication of the physical instruments' prototypes, but in very few cases, it was used in the actual generation or enhancement of sound, with the instruments relying almost exclusively in acoustic and mechanical sound.
GSCC: 0000000

SHAPED BY USE - Individual designs reshaping the city - Soares, Nuno (2017)
Macau is the most densely populated territory in the world, a small but complex urban landscape populated by a myriad of informal devices that produce a dramatic impact on the image and use of the city, creating an ever-present layer shaped by use. The traditional fields of architectural and urban morphology base their analysis on the private and public space, on the forms of buildings, block, streets, and squares. However, the urban landscape is not only shaped top down by market forces, governments, institutional players, but also bottom-up by thousands of small scale interventions carried out daily by their inhabitants, to solve problems or seize opportunities, on the normal process of usage. This research summarizes an extensive analysis of Macau’s urban landscape focused on this layer of appropriation, aimed to identify these shapes generated by use or, in other words, the devices that materialize the phenomenon of appropriation of the public space. They can take the shape of window cages, rooftop houses, canopies, annexes, hawker booths, and outdoor ads. SHAPED BY USE Individual designs reshaping the city – is a typo morphological essay aimed to provide a methodological tool for the analysis of such phenomena, both in this and other similar urban contexts as well as a compelling starting point to speculate on how small scale individual designs can contribute to reactivate and be harnessed to positively reshape the city.

Semiotic multimodality :a filmic analysis of Wong Kar-Wai's in the mood for love / - Tan, Chee Seng (University of Saint Joseph, 2017)
The study builts on Bateman and Schmidt’s (2011) and Tseng’s (2009) research on film as a form of “cinematographic document,” and continues their efforts to construct a semiotic mode of film. The author recognizes the complexity of undertaking research in the domain of semiotic discourse. This study argues that as film analysis is about ways of seeing and synthesizing different cinematic styles, strategies; learnt cinematic conventions and reflective viewing is imperative. The interaction of robust multimodal resources, well-defined analytic units, based on dependable models, and conducted through a discursive process should align to produce fruitful filmic discourse. The study premised on the assumption that film is more than a “self-enclosed signification system” but a crucial “cultural practice” that “reflect and inflect culture.” Taken together, this view underscores the importance and interactivity of cinema, culture and society. To this end, the study contributes to filmic meaning making, the New Hong Kong Cinema, and finally, the present study invariably serves as a form of “social document” or “cultural artifacts” in its exploration of Hong Kong ever changing identity, culture and moods.
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Redesigning historic cities facing rapid tourism growth: The Case of Macao’s World Heritage Centre and San Ma Lou Avenue - Pinheiro, Francisco Vizeu (Worldwide Hospitality and Tourism, 2017)

Preserving Cultural Identity by Rehabilitation of Public Spaces, Case Study Analyses on the Historic Center of Macao. - Pinheiro, Francisco Vizeu (Urban Design, 2017)

Poesia e navegação: o impacto da história e do mito na definição de uma poética especificamente portuguesa - Borges, Vera (De Portugal a Macau. Filosofia e literatura no diálogo das culturas, 2017)
Maria Celeste Natário, Renato Epifânio, Carlos Ascenso André, Gonçalo Cordeiro, Inocência Mata, Jorge Rangel, Maria Antónia Espadinha

Overall Opinion on Macau Urban Planning and the Five-Year Plan. - Pinheiro, Francisco Vizeu; Penny, W. (Journal of Macau Studies- Boletim de Estudos de Macau, 2017)

Macau Shaped by Use - Vernacular Customization of the City - Choi, Helen Hejung; Pai, Hyungmin (Imminent Commons: Commoning Cities", Seoul Biennale of Srchitecture and Urbanism, 2017)

Macao Shaped by Use –Formalizing the Vernacular Customization of the City in Choi, H. & Pai, H. (ed.) - Soares, Nuno; F., Simões (Imminent commons: commoning cities, 2017)

Macao Shaped by Use –Formalizing the Vernacular Customization of the City in Choi - Soares, Nuno; Simões, F. (Imminent Commons: Commoning Cities: Seoul Biennale of Architecture and Urbanism, 2017)

Impacts of Public Support and Voices Pluralism in Macao Newspapers - Simões, José Manuel; Faustino, Paulo (Journalism and Mass Communication, 2017)
0 citations (Crossref) [2022-09-21]

Entre a tradição e a modernidade, os Potiguara. Estudo etno-histórico, narrativas de memórias e rituais, a revisitação e o turismo - Simões, José Manuel (História, histórias, 2017)
0 citations (Crossref) [2022-09-21] Number: 10
Keywords: transformações

Editorial - Castro, Maria Guilhermina; Palinhos, Jorge; Ribas, Daniel; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2017)
Number: 2

Early Notices Regarding Creole Portuguese in Former Portuguese Timor - Baxter, Alan N.; Cardoso, Hugo C. (Journal of Language Contact, 2017)
4 citations (Crossref) [2022-09-21]

Descobrimentos marítimos: miscigenação e preconceito em Senna Fernandes - Conde, Margarida (De Portugal a Macau. Filosofia e literatura no diálogo das culturas, 2017)

Depiction of the freedom of the press and access to sources of information for working journalists in Macau - Rato, Frederico; Simões, José Manuel; Flores, Rui (Macau Portuguese and English Press Association, 2017)

De Portugal a Macau: Filosofia e Literatura no Diálogo das Culturas - Natário, Maria Celeste; Espadinha, Maria Antónia (Universidade do Porto, Faculdade de Letras, 2017)

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Computer Literacy Teaching Using Peer Learning and under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, Joao (International Association for the Development of the Information Society, 2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this "relationship-first, learning-second" type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher's message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the "face giving" and it is directly based on the relationship intensity to "help friends". At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process. [For the complete proceedings, see ED579282.]
Publication Title: International Association for Development of the Information Society ERIC Number: ED579300
Keywords: Action Research; Asian Culture; Case Studies; College Students; Computer Literacy; Confucianism; Cooperative Learning; Cost Effectiveness; Cultural Influences; English (Second Language); Foreign Countries; Grades (Scholastic); Language of Instruction; Models; Participant Observation; Peer Relationship; Peer Teaching; Program Effectiveness; Qualitative Research; Questionnaires; Semi Structured Interviews; Student Attitudes; Student Journals; Student Surveys; Teaching Methods

Charter UIA/UNESCO for Architectural Education - Mohamed, E.; Soares, Nuno; Revedin, J. (International Union of Architects, 2017)

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (Proceedings of the 8th International Conference on Digital Arts, 2017)
2 citations (Crossref) [2022-10-27]

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts (ARTECH 217), 2017)
0 citations (Crossref) [2022-09-21] GSCC: 0000000